(untitled) (Orfeu, 2022)
This paper presents the results of a mapping of the Artistic Research’s academic production in music between 2010 and 2020. For this, we stablish as search places the proceedings of ANPPOM, SIMPOM and ABRAPEM conferences and the journals Música Hodie, Per Musi, Opus and Vórtex. At the end of this search, we found 45 papers that attended the stablished criteria. This production is presented and analyzed in this paper from its nature and places of publication, from the theoretical basis used and from the analysis of its keywords. Based on these three elements we could comprehend the peculiarities of music Artistic Research in Brazil and relate it with the production outside the country, presenting Artistic Research as a polysemic term and listing come possible paths.